2018
DOI: 10.1007/s10212-018-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the self-referent executive processing model of test anxiety: control, emotional regulation, self-handicapping, and examination performance

Abstract: According to the self-referent executive processing (S-REF) model, test anxiety develops from interactions between three systems: executive self-regulation processes, selfbeliefs, and maladaptive situational interactions. Studies have tended to examine one system at a time, often in conjunction with how test anxiety relates to achievement outcomes. The aim of this study was to enable a more thorough test of the S-REF model by examining one key construct from each of these systems simultaneously. These were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 75 publications
2
31
0
6
Order By: Relevance
“…Positive activating emotions (enjoyment, hope, pride) were reported to be interrelated with metacognitive monitoring processes in multimedia learning tasks, but negative emotions (frustration) and deactivating emotions (boredom) have been shown to negatively predict self-monitoring [31]. Elsewhere, the negative impact of test anxiety has been verified, and potential control mechanisms have been explored [32]. The effect of rumination on university students' negative affect and on their achievement has also been confirmed [33].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 97%
See 1 more Smart Citation
“…Positive activating emotions (enjoyment, hope, pride) were reported to be interrelated with metacognitive monitoring processes in multimedia learning tasks, but negative emotions (frustration) and deactivating emotions (boredom) have been shown to negatively predict self-monitoring [31]. Elsewhere, the negative impact of test anxiety has been verified, and potential control mechanisms have been explored [32]. The effect of rumination on university students' negative affect and on their achievement has also been confirmed [33].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 97%
“…Pekrun [32] went beyond previous conceptualizations [33,34] to classify academic emotions along three axes: their focus, valence, and activation (for an overview, see [35]). The source (focus) of academic or achievement emotions can be either the: (a) activity, relating to ongoing activities involved in achieving, or the (b) outcome, pertaining to concerns about achievement outcomes [25].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 99%
“…There is also evidence from individual studies for constructs that have not yet been included in metaanalyses that test anxiety is positively correlated with a bias towards threat perception (e.g., Putwain, Langdale, Woods, Nicholson, 2011), messages from teachers about the importance of avoiding failure (e.g., Putwain & Symes, 2011), and parental pressure (e.g., Putwain, Woods, & Symes, 2010). It is a notable limitation of the contemporary test anxiety literature, however, that there are few systematic evaluations of the aforementioned theories (for a notable exception see Putwain, 2018).…”
Section: Test Anxiety Antecedents and Outcomesmentioning
confidence: 99%
“…Among academic stressors, three main groups can be distinguished: (1) those related to evaluation processes, (2) those related to work overload, and (3) other conditions of the teaching-learning process, such as social relationships (teacher-student and peer relationships), teaching methodology, and various organizational components (inadequate study plans, scheduling problems, overlapping programs, low student participation in organization and decision making, overcrowding, etc.) (GonzĂĄlez-Cabanach et al, 2016, 2017, 2018. Denovan and Macaskill (2013), in a study that lists 11 potential situations that generate stress and stress symptoms, found that the situations predictive of chronic stress were class participation, required assignments, and test taking.…”
Section: Factors Of Academic Stress In the Teaching-learning Processmentioning
confidence: 99%